Invertebrate community responses to a particulate‐ and dissolved‐copper exposure in model freshwater ecosystems. (23rd September 2014) - Gardham, Stephanie; Chariton, Anthony A.; Hose, Grant C.
Abstract: Historical contamination has left a legacy of high copper concentrations in the sediments of freshwater ecosystems worldwide. Previous mesocosm studies have focused on dissolved‐copper exposures in the overlying waters, which, because of altered exposure pathways, may not accurately predict the effects of copper exposure on invertebrate communities at historically contaminated sites. The present study assessed the effects of copper on the establishment of invertebrate communities within a large outdoor pond mesocosm facility containing environmentally relevant copper‐spiked sediments. High particulate copper concentrations (>400 mg/kg dry wt) caused a pronounced effect on the benthic community richness, abundance, and structure in the mesocosms, but particulate copper concentrations below 100 mg/kg dry weight had no effect. Furthermore, there were no effects of copper on the invertebrate communities within the water column, even in the highest copper treatment. The response of the benthic community to copper was influenced by interspecific interactions, the stage of ecological succession, and interspecies variation in sensitivity to copper. The present study demonstrates the importance of using environmentally realistic exposure scenarios that provide both particulate and dissolved exposure pathways. It also emphasizes that risk assessments for aquatic ecosystems should consider the influence of interspecific interactions and interspecies variation in driving the biotic response to contamination. Environ Toxicol Chem 2014;33:2724–2732 . © 2014 SETAC